Role of housing in welfare of small ruminants (Indian Journal of Animal Production and Management, 2016)
Scientific research on factors causing the  reduction in welfare of sheep and goats is rather  recent and information on this topic is still scarce.  Sheep and Goats, considered very rustic animals,  are reared prevalently under extensive production  systems and are widespread mainly in marginal  areas. For these reasons, only few studies on the  welfare of these species have been carried out in the  past. Climatic extremes and seasonal fluctuations in  herbage amount and quality are important causes of  the reduction of well-being in extensive production  systems, which can impair production efficiency of  grazing animals and dramatically affect the welfare  and health status of sheep and goats. More recently,  the scenario has changed, due to a gradual diffusion  of intensive and semi-intensive production systems,  especially in sheep and goats to the growing concern  of consumers. Research addressing animal welfare  is largely focused on measurements of animal  behavior, stress physiology, veterinary epidemiology,  environmental physiology, environmental design,  comparative psychology and studies of the behavior  of animal handlers, together with conventional fields  such as nutrition and microbiology16, 17, 29.